Boosting the lithium and sodium storage performance of graphene-based composite via pore engineering and surface protection. (16th December 2020) - Wu, Hefeng; Gan, Yanmei; Yao, Qianqian; Wang, Luyuan Paul; Wang, Chaoying; Zhang, Qixin; Hou, Kun; Zhao, Yi; Guan, Lunhui
Abstract: Transition metal oxides with high theoretical capacities are widely investigated as potential anodes for alkali-metal ion batteries. However, the intrinsic conductivity deficiency and large volume changes during cycles result in poor cycling stability and low rate capabilities. Graphene has been widely used to support metal oxide for enhanced performance, but the cycling life is limited by the aggregation/collapse of active materials on graphene surface. Herein, we significantly improve the battery performance of graphene-metal oxide composite via pore engineering and surface protection. In this architecture, the mesoporous NiFe2 O4 is designed for fast ion diffusion and volume accommodation, and the outer graphene protection can further enhance the electrical conductivity and prevent the aggregation during cycle. Thus, as-prepared G@p-NiFe2 O4 @G composite for lithium storage delivers high capacity (1244 mA h g −1 after 300 cycles at 0.2 A g −1 ), excellent rate performance (563 mA h g −1 at 4 A g −1 ), and outstanding cycling life up to 1200 cycles at 1.5 A g −1 . For sodium storage, it also displays good cycling stability and superior rate performance. Moreover, the effects of various microstructures on the battery performance, the reaction kinetics of various electrodes, and the reaction mechanism of NiFe2 O4 have been systematically investigated in this work.